Formulary apportionment in the European Union – future research agenda - Mlčúchová, Markéta (Economics and Business Review, 2023)
This paper is focused on the Formulary Apportionment, to be used within the European Union, hence, to replace the Separate Accounting and arm’s length principle. Reflecting upon the announced European Commission’s Proposal for new framework for business taxation and the foreseeable upswing of the academic discussion focused on the Formulary Apportionment methodology, this paper represents the first systematic literature review on this topic. The main aim of the paper is to identify the relevant prior research, explore the current literature and develop directions for future research. The study identifies eight main thematic clusters, provides an interpretative framework, and suggests valuable future research directions within each thematic cluster as well as general future research agenda.